Finding time : how corporations, individuals, and families can benefit from new work practices - Perlow, Leslie A. (Cornell University P. New YorkUS, 1997)
Uses data collected from the study of a group of engineers to explore workers' perceptions of what employers expect of them; and the resulting importance that they (workers) ascribe to working long hours and doing high-visibility work. Discusses the effects of workers' compliance with these expectations, on themselves and their families. Looks at how factors such as interruptions, and the crisis mentality impact on workers' use of their time at work, and the negative effects of these factors on corporate productivity. Discusses the potential benefits of new work practices for workers, their families and their corporations.